WASTE BANK DEVELOPMENT : MENUJU EKOSISTEM PESANTREN INKLUSIF KEUANGAN SYARIAH DENGAN KONSEP EKONOMI SIRKULAR - Rahma Apriani; Ruslan Abdul Ghofur; Heni Noviarita (LPPM STIE Muhammadiah Bandung, 2025)
Islamic boarding schools have become an important pillar in the social and spiritual development of Indonesian society. In addition to being a center for religious education, Islamic boarding schools also have great potential in developing community-based economic activities. In this context, the role of Islamic boarding schools in supporting the sustainable development agenda is increasingly receiving attention, especially through strengthening economic independence and financial inclusion. The collaboration between the At-Tanwir Islamic Boarding School in Metro City, Bank Sampah, and Bank Syariah Indonesia is a form of strategic synergy that stems from concern for two main issues: inequality in access to finance and environmental problems. This research is a descriptive qualitative study with an exploratory case study (Creswell and Creswell, 2017). This study examines in depth the phenomenon of the integration of the circular economy and Islamic finance in one specific location (At-Tanwir Islamic Boarding School). This study shows that the integration of Islamic boarding school-based waste banks with Islamic financial services is able to create an inclusive, participatory, and sustainable economic ecosystem. The active role of students, support from Islamic boarding schools, and facilitation from Bank Syariah Indonesia are the keys to the success of this model. This practice proves that the circular economy and Islamic finance can go hand in hand, and Islamic boarding schools have the potential to become pioneers in developing a green economy based on Islamic values